Fast recovery of house infestation with Triatoma brasiliensis after residual insecticide spraying in a semiarid region of Northeastern Brazil. - Claudia Mendonça Bezerra; Silvia Ermelinda Barbosa; Rita de Cássia Moreira de Souza; Levi Ximenes Feijão; Ricardo Esteban Gürtler; Alberto Novaes Ramos; Liléia Diotaiuti (Public Library of Science (PLoS), 2020)
The northeastern semiarid region stands out in the Brazilian context regarding the eco-epidemiology of Chagas disease, in which Triatoma brasiliensis is the main vector of Trypanosoma cruzi. Persistent house invasion threatens the relative levels of progress achieved over previous decades. We conducted an intervention trial with a five-year follow-up to assess the impacts of residual spraying with pyrethroid insecticides on house infestation with T. brasiliensis in 18 rural villages (242 houses) located in the Tauá, Ceará. House infestations were assessed by systematic manual searches for triatomines in every domestic and peridomestic habitat on five occasions. Triatomines were collected in peridomestic (57.5%), sylvatic (35.8%), and intradomiciliary (6.7%) habitats. The most important ecotopes of T. brasiliensis were containing roofing tiles, bricks or rocks (23.4% ± 9.1). Residual insecticide spraying substantially reduced baseline house infestation rates from 27.9% to 5.9% by 6 months post first spraying (MPS). The decline was substantially greater in intradomiciles (11.2% to 0.8%) than in peridomiciles (16.7% to 5%). The mean relative density of triatomines recovered its preintervention values at 14 MPS in intradomiciles, and in the main peridomestic ecotopes. The house infestation levels recorded at 14 MPS persisted thereafter despite all reinfested houses were selectively sprayed on every occasion. Overall average bug infection rates with T. cruzi in the five occasions were in intradomiciles (11.1%), peridomiciles (4.7%) and wild habitats (3.3%). In peridomicile T. cruzi infection rates decreased significantly at all stages after chemical intervention. In intradomicile, the only significant difference occurred at 20 MPS (7.7% to 30.8%). The vectorial capacity of T. brasiliensis, combined with its invasive potential from sylvatic sources and the limited effectiveness of chemical control in the harsh caatinga landscape, pose serious obstacles to the definite elimination of domestic transmission risks. Systematic vector surveillance supported by community participation and locally adapted environmental management measures are needed to reduce the risks of establishment of domestic transmission with T. cruzi in this region.